Ethnogynaecological uses of plants from Gujarat, India - Patel, P.K.; Patel, M.K. (Bangladesh Journal of Plant Taxonomy, 2012)
Not available. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10947 Bangladesh J. Plant Taxon. 19(1): 93-94, 2012 (June)